Antibiotics alter the window of competence for natural transformation in streptococci. (27th August 2018) - Sturød, K.; Salvadori, G.; Junges, R.; Petersen, F.C.
Summary: Streptococcus pneumoniae transformation occurs within a short competence window, during which the alternative sigma factor X (SigX) is activated to orchestrate the expression of genes allowing extracellular DNA uptake and recombination. Importantly, antibiotic stress promotes transcriptional changes that may affect more than 20% of the S. pneumoniae genome, including competence genes. These can be activated or repressed, depending on the antibiotic agent. For most antibiotics, however, it remains unknown whether transcriptional effects on competence translate into altered transformability. Here we investigate the effect of antibiotic subinhibitory concentrations on sigX expression using a luciferase reporter, and correlate for the first time with transformation kinetics. Induction of sigX expression by ciprofloxacin and novobiocin correlated with increased and prolonged transformability in S. pneumoniae . The prolonged effect of ciprofloxacin on competence and transformation was also observed in the streptococcal relatives Streptococcus mitis and Streptococcus mutans . In contrast, tetracycline and erythromycin, which induced S. pneumoniae sigX expression, had either an inhibitory or a nonsignificant effect on transformation, whereas streptomycin and the β‐lactam ampicillin, inhibited both sigX expression and transformation. Thus, the results show that antibiotics may vary in their effects on competence, ranging from inhibitory to stimulatory effects, and that responses affecting transcription of sigX do not always correlate with the transformation outcomes. Antibiotics that increase or decrease transformation are of particular clinical relevance, as they may alter the ability of S. pneumoniae to escape vaccines and antibiotics.